A escola seletiva como problema educacional uma leitura da Revista Brasileira De Estudos Pedagógicos (1952–1961) - Silva, Fernanda Marques Da [UNIFESP] (2020)
The present dissertation refers toa historical documentary research that adopts the Brazilian Journal of Pedagogical Studies(Revista Brasileira de Estudos Pedagógicos – RBEP),as the main research source, created in 1944 and linked to the National Institute for Educational Research (Instituto Nacional de Pesquisas Educacionais – Inep), to expose and analyze the way in which, between the years 1952 and 1961, failure, repetition, dropout, and school deficits were addressed in this journal, elements that express school failure and that were taken, in this research, as characteristic of the selective primary school. The time frametakes into account the period in which Inep was directed by Anísio Teixeira —a time when educational research intensifies, movements around the democratization of education, and, consequently, the discussions about school selectivity. It is also in this period that the debates take place for the drafting of the National Education Guidelines and Bases Law (Lei de Diretrizes e Bases da Educação Nacional – LDB), Law 4024/61, which would define the direction of education in the country. We select, in the period considered, the articles of RBEP that discuss, directly or indirectly, the selectivity of the school and the problems that define it. We identify the respective authors of the articles, causes pointed out by them for these problems, and the proposals to facing them. The results reveal, in the narratives constructed by the authors, representations that sought to give meaning and visibility to the debate that placed the school primary as an extremely selective institution. Show wide discussion of issues related to school selectivity, treated preferentially as due to the inadequacy and insufficiency of the school, highlighting problems related to the training and performance of teachers, the organization of the school, and education systems. These representations also show the existence of a group of authors — technicians, researchers and teachers — who held positions in the educational administration, higher education, or research educational institutions. Thus, the research reveals, from the investigation of the trajectory and performance of the authors at the time, who besides forming a group or a community and sharing projects for education and common ideals, although not univocal, the authors build a way of looking at the problems of the selective school that is directly related to the positions they occupy. None of them worked in primary school and directly held the student or his family responsible for the failure of school. The fact of considering failures, repetition, abandonment, and deficit school as characteristic aspects of the selective school, reveals that they considered these problems a disturbance of the system itself, to which they haveattributed the responsibility for the selectivity of the primary school.